"Moiwa fa ba bangwe The imperative to generosity and caring - a challenge to the Hervormde Kerk in Suidelike Afrika 1 - Manala, Matsobane J. (HTS teologiese studies, 2001)
In this article, the Afro-Christian imperative of caring and sharing is highlighted as a fundamental response of the church, as the body of Christ, in the face of abject poverty. The extent of poverty in South Africa is sketched, both as an economically and as a socio-spiritualy destructive phenomenon. Based on Biblical perspectives, theological principles underlying benevolent services within Reformed churches are outlined and evaluated.